How to read Chinese poetry workbook : a guided anthology - Cui, Jie (Columbia University Press, 2012)
Ebook from IG Library; Includes bibliographical references and indexes; Designed to work with the acclaimed course text How to Read Chinese Poetry: A Guided Anthology, the How to Read Chinese Poetry Workbook introduces classical Chinese to advanced beginners and learners at higher levels, teaching them how to appreciate Chinese poetry in its original form. Also a remarkable stand-alone resource, the volume illuminates China's major poetic genres and themes through one hundred well-known, easy-to-recite works